Selinexor—A Drug Review - Jayamohanan, Hridya; Venniyoor, Vaibhav; Pavithran, Keechilat (Indian Journal of Medical and Paediatric Oncology, 2021)
Selinexor developed by Karyopharm Therapeutics is the first orally available small-molecule inhibitor of exportin-1 (XPO1). XPO-1 is a protein transporter responsible for the export of macromolecules such as tumor suppressor proteins and oncoprotein mRNAs from the nucleus to the cytoplasm; its inhibition results in blocking of multiple oncogenic pathways. Overexpression of XPO1 is seen in multiple myeloma and various other malignancies and is a poor prognostic marker. Pivotal positive trials have resulted in the approval of selinexor for use in refractory or relapsed diffuse large B cell lymphoma and multiple myeloma. In this review, we briefly cover the drug development, mechanism of action, indications, and toxicities of the drug, and the major pivotal trials.
Keywords: selinexor; XPO-1; oncoprotein; multiple myeloma